An Innovation of Hearing Aid - MOHAMAD, ZUNUWANAS; BINTI MUSTAPHA, SITI NUR AFIQAH; BIN YUSSOP, MOHD HAFIZUL; BIN MOHD ZUHAIRI, MUHAMMAD SYAMIM ARIF (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2023)
– The human ear is an organ of hearing and balance. It detects and analyzes sound through a transduction mechanism, which is the process of converting sound waves into electrochemical impulses. Auditions cannot be adequately performed if the anatomy is abnormal. Hearing aids are small amplifiers that fit into the ear, used by people who are partially deaf. In this effort, adaptive hearing aids have been designed to improve hearing for the deaf. To improve hearing for deaf people, it should correct speech imperfections and adjust the volume of acoustic impulses intelligently. With the use of electret microphones, the sound is recorded from all sides. The signal emanating from it is first amplified using a low-pass filter. This paper is to diagnose the patient case scenario for the hearing-impaired patient, to identify the wearability issue of the patient's hearing aid. At the same time study, the theory of hearing loss and find out the causes of hearing loss, and provide a proposal for the design of suitable equipment for the study (3D). For this reason, we propose to make improvements to the old hearing aids by adding a volume knob